Septemtrionaliora Americae à Groenlandia, per Freta Davidis et Hudson, ad Terram Novam - Wit, Frederick de, 1630-1706 ([Amsterdam?], 1675)
Colour. Compass rose and rhumb lines. Two decorative title cartouches. Bar scales in German miles, "mitaria geometrica," French miles and "milaria Gallica." CNS map no. 286.